2023
DOI: 10.1021/jacs.3c02331
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a C2-Symmetric Chiral Borinic Acid and Its Application in Catalytic Desymmetrization of 2,2-Disubstituted-1,3-Propanediols

Abstract: Notwithstanding the common use of boronic acids in catalysis, the design and synthesis of efficient chiral boronic acids remains a formidable challenge. Herein we disclose a rational design and a concise synthesis of a series of novel C 2-symmetric disubstituted boronic acids, or borinic acids. Chiral borinic acids have been found to be excellent agents that can achieve highly enantioselective desymmetrization of 2,2-disubstituted-1,3-propanediols, providing chiral diols with a quaternary stereocenter, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Organoboron acids are also potent catalysts for the regioselective modification of polyols. A common mechanism involves the selective recognition and activation of the cis -1,2-diol structure of polyols via tetra -coordinated boronate formation, which is a catalytically active intermediate (Figure ). This concept of diol activation was pioneeringly established by Aoyama and co-workers with a stoichiometric amount of boronic acids (Figure A). , Currently, this reaction strategy has been elaborated as a catalytic reaction (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…Organoboron acids are also potent catalysts for the regioselective modification of polyols. A common mechanism involves the selective recognition and activation of the cis -1,2-diol structure of polyols via tetra -coordinated boronate formation, which is a catalytically active intermediate (Figure ). This concept of diol activation was pioneeringly established by Aoyama and co-workers with a stoichiometric amount of boronic acids (Figure A). , Currently, this reaction strategy has been elaborated as a catalytic reaction (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…The use of organoboron compounds as catalysts is attractive because of their ability to predict accurate regioselectivity . In 2011, Taylor reported the first organoboron-catalyzed regioselective modification and glycosylation of carbohydrates using diarylborinic acid as the catalyst. , Based on this pioneering research, regioselective molecular transformations with organoboron compounds, including cyclic borinic acids, boronic acids, and benzoborols, as catalyst have been reported. , Recent advances in this field involves hybrid catalysis, combining organoboron and transition metal complex for regioselective functionalizations of carbohydrates. , Notably, Niu demonstrated a site-divergent terminal propargylation of carbohydrates using a borinic acid/copper hybrid catalytic system . Exploring a similar concept, they discovered site-switchable mono- O -allylation of polyols with Lewis acid/palladium cocatalyst system. Loh et al reported synergistic chiral organoboron/rhodium­(I)-catalyzed regioselective functionalization of carbohydrates …”
mentioning
confidence: 99%
“…Chirality is ubiquitous in nature ranging from macroscopic to microscopic systems, with implications for biological and physiological processes. The concept of chirality has therefore infiltrated numerous areas of research including pharmaceuticals, bioengineering, agriculture and biosensing. Due to their chiroptical activity and self-assembling capabilities, chiral inorganic nanostructures especially have been a key ingredient in optoelectronics, sensors, and enantioselective catalysis. These biomimetic nanoparticles display both molecular and nanoscale chirality, corresponding to the geometry of surface ligands and of the nanoparticles as a whole. By unraveling chirality-dependent interactions on the nano- and molecular scale, these developments have helped us better understand how chirality is selected in biological systems and demonstrated the potential for chiral nanostructures in life science. Some of the widely used chiral two-dimensional (2D) materials toward this direction are graphene, boron nitride, graphitic carbon nitride, transition metal dichalcogenides, phosphorene, etc. , Borophene, a relatively newer addition to the portfolio of 2D nanomaterial, demonstrates unique chemical and metallic properties with varied structural polymorphism. The polymorphic nature of borophene, is derived from the bonding configurations among boron atoms, which further distinguishes it from other 2D materials and allows for customization of its material properties. , One of the other interesting facts for this emerging boron allotrope is behind its anisotropic Dirac properties that are hypothesized to largely influence biological interactions. However, imepdiment in imparting chirality to such materials, the challenge of sustainability, purity of enantiomers, solubility, and stability are growing concerns. Scientists have generally used enantioselective organic–inorganic interactions, template-induced synthetic approaches, and photon-induced methods to introduce chirality in nanomaterials. ,…”
mentioning
confidence: 99%